MARKETING AUDIT OF EDUCATIONAL SERVICE COMPANY - Surya, Mulyana; Machfud, Machfud; Simanjuntak, Megawati (Universitas Brawijaya, Indonesia, 2019)
The Nurul Fikri Study Guidance and Consultation Institute (BKB NF), as a business entity, must periodically conduct marketing audits and business strategies. This research (marketing audit) uses a quantitative approach to the case or object of research in the form of a Tutoring Education Institute. The object of research is the BKB NF Institute, with respondents from all levels of management / structural employees of BKB NF throughout Indonesia. The instrument in the form of Competitive Setting Profile (CSP) and Company Alignment Profile (CAP) questionnaires, distributed via google form. The questionnaire was filled in self-report / assessment using management judgment. Data analysis used the framework of Strategic Marketing Plus 2000. The results of calculations resulted in a CSI of 4.12, interpreted the competitive situation faced by the sophisticated stage BKB NF. CAI NF of 2.93, interpreted the existing marketing type of BKB NF is segmented marketing. CAI<CSI means that the existing marketing type lags 1.19 points compared to its competitive set. BKB NF must change its marketing type to niche marketing, including nine elements of strategy (segmentation, targeting, and positioning), tactics (differentiation, marketing mix, and selling), and value (brand, service, and process).